Assessing the roles of temperature, precipitation, and enso in dengue re-emergence on the Texas-Mexico border region Evaluación del clima y del ENSO en la reemergencia del dengue en la frontera Texas-México - Joan M Brunkard; Enrique Cifuentes; Stephen J Rothenberg (Instituto Nacional de Salud Pública, 2008)
OBJECTIVE: The goal of this study was to assess linkages between microclimate and longer-term ENSO-related weather forcing on the week-to-week changes in dengue prevalence in Matamoros, Tamaulipas, Mexico, over a recent decade of dengue observations. MATERIAL AND METHODS: An auto-regressive model to evaluate the role of climatic factors (sea-surface temperature) and weather (maximum temperature, minimum temperature, precipitation) on dengue incidence over the period 1995-2005, was developed by conducting time-series analysis. RESULTS: Dengue incidence increased by 2.6% (95% CI: 0.2-5.1) one week after every 1ºC increase in weekly maximum temperature and increased 1.9% (95% CI: -0.1-3.9) two weeks after every 1 cm increase in weekly precipitation. Every 1ºC increase in sea surface temperatures (El Niño region 3.4 ) was followed by a 19.4% (95% CI: -4.7-43.5) increase in dengue incidence (18 weeks later). CONCLUSIONS: Climate and weather factors play a small but significant role in dengue transmission in Matamoros, Mexico. This study may provide baseline information for identifying potential longer-term effects of global climate change on dengue expected in the coming decades. To our knowledge, this is the first study to investigate the potential associations between climate and weather events and dengue incidence in this geographical area. OBJETIVO: Evaluar los vínculos entre el microclima, las variables relacionadas al fenómeno de El Niño Oscilación del Sur (ENSO) y los cambios en el reporte semanal de casos de dengue en el área de Matamoros, Tamaulipas, México, a lo largo de una década de observaciones. MATERIAL Y MÉTODOS: Se desarrolló un modelo autorregresivo para evaluar la influencia de factores climáticos (temperatura superficial del mar) y tiempo (temperatura máxima, temperatura mínima y precipitación) sobre la incidencia de dengue, a lo largo de 11 años (1995-2005), empleando análisis de series de tiempo. RESULTADOS: La incidencia de casos de dengue aumentó 2.6% una semana después de cada 1ºC de incremento en la temperatura máxima semanal (95% IC: 0.2, 5.1); observamos también que los casos de dengue aumentaron 1.9% dos semanas después de cada centímetro de incremento en la precipitación semanal (95% IC: -0.1, 3.9). Cada 1ºC de aumento en la temperatura superficial del mar en la región Niño 3.4 fue seguida, 18 semanas después, de un aumento de 19.4% en la incidencia de casos de dengue (95% IC: -4.7, 43.5). CONCLUSIONES: Los factores de clima y tiempo tienen una influencia menor, aunque significativa, sobre la transmisión del dengue en la ciudad fronteriza de Matamoros, México. Este estudio aporta información basal para identificar efectos potenciales de mayor alcance, relacionados con el cambio climático global sobre los casos esperados de dengue en las próximas décadas. Hasta donde sabemos, este es el primer estudio que evalúa las posibles asociaciones entre los eventos climáticos y tiempos y la incidencia de casos de dengue en la frontera de México con Texas.